Of Microbes and Minds: A Narrative Review on the Second Brain Aging - Calvani, Riccardo; Picca, Anna; Lo Monaco, Maria Rita; Landi, Francesco; Bernabei, Roberto; Marzetti, Emanuele (Frontiers in Medicine, 2018)
In recent years, an extensive body of literature focused on the gut-brain axis and the possible role played by the gut microbiota in modulating brain morphology and function from birth to old age. Gut microbiota has been proposed as a relevant player during the early phases of neurodevelopment, with possible longstanding effects in later life. The reduction in gut microbiota diversity has also become one of the hallmarks of aging, and disturbances in its composition are associated with several (age-related) neurological conditions, including depression, Alzheimer's and Parkinson’s diseases. Several pathways have been evoked for gut microbiota-brain communication, including neural connections (vagus nerve), circulating mediators derived by host-bacteria co-metabolism, as well as the influence exerted by gut microbiota on host gut function, metabolism and immune system. Although the most provoking data emerged from animal studies and despite the huge debate around the possible epiphenomenal nature of those findings, the gut microbiota-brain axis still remains a fascinating target to be exploited to attenuate some of the most burdensome consequences of aging.